Pelaksanaan Multi Metode untuk Meningkatkan Pembelajaran yang sesuai dengan Pelajaran Matematika dan PKn di Kelas IV Sekolah Dasar - Oktasilvia, Resi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
Learning outcomes can be influenced by the method used by the teacher during the learning process. The purpose of the study was to describe and analyze the impact of implementing multi-methods in accordance with Mathematics and Civics lessons on student learning outcomes. This research is a Classroom Action Research (CAR). The research subjects were Class IV students of SDN 20 Sitiung as many as 25 people in the 2020/2021 academic year. The technique of collecting data is by carrying out an assessment in 3 cycles and each cycle includes planning, implementation, observation and reflection with a student learning outcome of at least 60. The test scores for Mathematics and Civics subjects show that there is an increase in each cycle, in this case the success of learning objectives and students' KKM achieve a predetermined value of 60 in Mathematics and 70 in Civics. Based on the results and discussion, it can be concluded that the implementation of learning Mathematics and Civics in grade IV students of SDN 20 Sitiung using multiple methods and variants of teaching aids there is a good change in grades.